The effectiveness of the discovery and the expository approaches in the teaching of social studies in a rural high school - Caballero, Victorina Liongson 1950-
The author attempted to find out evidences that would show the effectiveness of the discovery and expository approaches in the teaching of social studies in a rural high school.